Leading q T /Q correction for Drell-Yan process in TMD factorization - Arturo Arroyo-Castro; Ignazio Scimemi; Alexey Vladimirov (Journal of High Energy Physics)
Abstract The transverse momentum dependent (TMD) factorization theorem accommodates various types of power corrections. Among them, the least studied are q T /Q corrections, which become significant at large values of transverse momentum. These corrections partially originate from higher-twist TMD distributions, which exhibit singularity at small transverse distances. We propose a decomposition that reveals this singularity explicitly, and makes the q T /Q correction manifest. As a concrete application, we consider the next-to-leading power correction for the angular distributions in Drell-Yan, and determine the leading q T /Q corrections. These corrections are significant for the angular distributions A 1 and A 3, in complete agreement with the data.